Preparation method of porous carbon material
By using the method of heat solution in the protective atmosphere using the use of cymbal blue and iron chloride, the problem of low production rate of existing pores of charcoal materials has been solved, and the high yield rate of porous charcoal materials and the feasibility of industrialized applications are realized.
Patent Information
- Application Number
- CN202411289151.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-24
AI Technical Summary
The yield of the existing porous carbon material preparation process is relatively low, only between 10% and 20%, and even if it is controlled by activator selection and pyrolysis conditions, the yield can only be increased to 40% and 50%.
Using indigo as a precursor and ferric chloride as an activator, pyrolysis is performed in a protective atmosphere to prepare porous carbon materials. The method includes mixing indigo and ferric chloride in a specific mass ratio, placing them in a nitrogen or argon atmosphere for pyrolysis, and then performing pickling, water washing and drying.
The ultra-high yield of porous carbon materials has been achieved, reaching more than 80%, and the process is atom-economical, simple to operate, and low in cost, making it suitable for large-scale industrial promotion and application.
Smart Images

Figure CN119349576A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous materials, and in particular to a method for preparing a porous carbon material. Background Art
[0002] Porous carbon materials have the advantages of large specific surface area, controllable pore structure, stable physical and chemical properties, good conductivity, etc. They are widely used in many fields such as energy storage and conversion, adsorption separation, catalysis, petrochemicals, etc., and are one of the key materials in modern industrial production processes. However, the yield of porous carbon materials in the existing porous carbon material preparation process is generally only 10% to 20%. Although the yield of porous carbon materials can be improved to a certain extent by selecting activators, controlling pyrolysis conditions and adopting specific preparation processes, it can only be increased to 40% to 50%, which is still relatively low.
[0003] Therefore, it is of great significance to develop a method for preparing porous carbon materials with atom economy, simple operation, low cost and ultra-high yield. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a porous carbon material.
[0005] The technical solution adopted by the present invention is:
[0006] A method for preparing a porous carbon material comprises the following steps: mixing indigo and ferric chloride and placing the mixture in a protective atmosphere for pyrolysis to obtain a porous carbon material.
[0007] Preferably, the mass ratio of indigo to ferric chloride is 1:0.1-10.
[0008] More preferably, the mass ratio of indigo to ferric chloride is 1:1-5.
[0009] Preferably, the protective atmosphere is a nitrogen atmosphere or an argon atmosphere.
[0010] Preferably, the pyrolysis is carried out at a temperature of 300° C. to 1500° C., and the pyrolysis time is 0.5 h to 5 h.
[0011] Further preferably, the pyrolysis is carried out at a temperature of 600° C. to 800° C., and the pyrolysis time is 1.5 h to 2.5 h.
[0012] Preferably, the product obtained by pyrolysis is further acid-washed, water-washed and dried.
[0013] Preferably, the acid solution used for pickling is one of hydrochloric acid, sulfuric acid and nitric acid.
[0014] Preferably, the concentration of the acid solution used in the pickling is 0.1 mol / L to 3.0 mol / L.
[0015] An electrode comprises the porous carbon material prepared by the method.
[0016] Preferably, the electrode further comprises a conductive material and a binder.
[0017] Preferably, the mass ratio of the porous carbon material to the conductive substance is 7 to 9:1.
[0018] Preferably, the conductive material is at least one of conductive carbon black, acetylene black, carbon nanotubes and graphene.
[0019] Preferably, the binder is polytetrafluoroethylene (PTFE).
[0020] A method for preparing the electrode as described above comprises the following steps:
[0021] 1) The porous carbon material, the conductive material and the binder solution are uniformly mixed, and then a demulsifier is added to perform demulsification to obtain a coating material;
[0022] 2) The coating material is applied onto the carrier, and then dried and compacted to obtain an electrode.
[0023] Preferably, the mass fraction of the binder solution in step 1) is 5% to 20%.
[0024] Preferably, the demulsifier in step 1) is at least one of ethanol and ether.
[0025] Preferably, in step 1), the mass ratio of the binder solution to the demulsifier is 1:1.0-1.2.
[0026] Preferably, the carrier in step 2) is one of nickel mesh, titanium mesh, stainless steel mesh and titanium foil.
[0027] Preferably, the drying in step 2) is carried out at a temperature of 60° C. to 150° C., and the baking time is 2 h to 12 h.
[0028] Preferably, the compaction in step 2) is carried out at a pressure of 15 MPa to 25 MPa, and the pressure holding time is 5 min to 10 min.
[0029] A supercapacitor comprises the electrode.
[0030] A lithium ion battery comprises the electrode.
[0031] The beneficial effects of the present invention are as follows: the present invention uses indigo as a precursor and ferric chloride as an activator to prepare porous carbon materials. It is an atom-economical, simple-to-operate, low-cost method for preparing porous carbon materials, which can achieve an ultra-high porous carbon material yield and is suitable for large-scale industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 1 is the nitrogen adsorption-desorption isotherm curve of the porous carbon material in Examples 1 to 9.
[0033] Figure 2 ] is the pore size distribution curve of the porous carbon material in Examples 1 to 9.
[0034] Figure 3 The cyclic voltammetry curves of the electrodes in Examples 1 to 3 are shown.
[0035] Figure 4 The cyclic voltammetry curves of the electrodes in Examples 4 to 6 are shown.
[0036] Figure 5 The cyclic voltammetry curves of the electrodes in Examples 7 to 9 are shown.
[0037] Figure 6 The constant current charge and discharge curves of the electrodes in Examples 1 to 3 are shown.
[0038] Figure 7 The constant current charge and discharge curves of the electrodes in Examples 4 to 6.
[0039] Figure 8 The constant current charge and discharge curves of the electrodes in Examples 7 to 9.
[0040] Fig. 9 The electrochemical impedance spectroscopy curves of the electrodes in Examples 1 to 3 are shown.
[0041] Fig.10 The electrochemical impedance spectroscopy curves of the electrodes in Examples 4 to 6 are shown.
[0042] Fig.11 ] are the electrochemical impedance spectroscopy curves of the electrodes in Examples 7 to 9. DETAILED DESCRIPTION
[0043] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0044] Embodiment 1:
[0045] A porous carbon material, the preparation method of which is as follows:
[0046] Indigo and ferric chloride are mixed in a mass ratio of 1:1 and loaded into a crucible, then placed in a tubular furnace, filled with nitrogen, and then heated from room temperature to 400°C at a heating rate of 1°C / min, and then continued to heat from 400°C to 600°C at a heating rate of 5°C / min, and kept warm for 2h. The pyrolysis product is then washed with 2mol / L hydrochloric acid, and then washed with deionized water until the washing liquid is neutral, and then placed in a constant temperature drying oven at 80°C for 24h to obtain a porous carbon material.
[0047] An electrode, the preparation method of which is as follows:
[0048] 1) the porous carbon material and the conductive carbon black are mixed uniformly at a mass ratio of 8:1 to prepare a powdered active substance, the powdered active substance and a 10% polytetrafluoroethylene aqueous solution are mixed uniformly at a mass ratio of 9:1, and anhydrous ethanol is added for soaking and demulsification to obtain a coating material;
[0049] 2) The coating material is applied on a nickel mesh (size: 1 cm×1 cm), and then placed in a constant temperature drying oven at 80°C for 4 hours, and then compacted at a pressure of 20 MPa for 5 minutes to obtain an electrode.
[0050] Embodiment 2:
[0051] A porous carbon material is exactly the same as Example 1 except that during preparation, "then the heating rate of 5°C / min is further increased from 400°C to 600°C" is adjusted to "then the heating rate of 5°C / min is further increased from 400°C to 700°C".
[0052] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used.
[0053] Embodiment 3:
[0054] A porous carbon material is identical to Example 1 except that the mass ratio of indigo and ferric chloride is adjusted from "1:1" to "1:2" during preparation.
[0055] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used.
[0056] Embodiment 4:
[0057] A porous carbon material, which is exactly the same as Example 1 except that the mass ratio of indigo and ferric chloride is adjusted from "1:1" to "1:2" and "then the heating rate of 5°C / min from 400°C to 600°C" is adjusted to "then the heating rate of 5°C / min from 400°C to 700°C".
[0058] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used.
[0059] Embodiment 5:
[0060] A porous carbon material is identical to Example 1 except that the mass ratio of indigo and ferric chloride is adjusted from "1:1" to "1:3" during preparation.
[0061] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used.
[0062] Embodiment 6:
[0063] A porous carbon material, which is exactly the same as Example 1 except that the mass ratio of indigo and ferric chloride is adjusted from "1:1" to "1:3" and "then the heating rate of 5°C / min from 400°C to 600°C" is adjusted to "then the heating rate of 5°C / min from 400°C to 700°C".
[0064] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used.
[0065] Embodiment 7:
[0066] A porous carbon material, which is exactly the same as Example 1 except that the mass ratio of indigo and ferric chloride is adjusted from "1:1" to "1:3" and "then the heating rate of 5°C / min from 400°C to 600°C" is adjusted to "then the heating rate of 5°C / min from 400°C to 800°C".
[0067] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used.
[0068] Embodiment 8:
[0069] A porous carbon material is exactly the same as Example 1 except that the mass ratio of indigo and ferric chloride is adjusted from "1:1" to "1:4" during preparation.
[0070] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used.
[0071] Embodiment 9:
[0072] A porous carbon material, which is exactly the same as Example 1 except that the mass ratio of indigo and ferric chloride is adjusted from "1:1" to "1:4" and "then the heating rate of 5°C / min from 400°C to 600°C" is adjusted to "then the heating rate of 5°C / min from 400°C to 700°C".
[0073] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used.
[0074] Comparative Example 1:
[0075] A porous carbon material is exactly the same as Example 2 except that the activator is replaced by sodium carbonate from ferric chloride during preparation.
[0076] Comparative Example 2:
[0077] A porous carbon material is exactly the same as Example 2 except that the activator is replaced by potassium carbonate instead of ferric chloride during preparation.
[0078] Performance Test:
[0079] 1) Nitrogen adsorption-desorption test: The porous carbon materials in Examples 1 to 9 were subjected to nitrogen adsorption-desorption tests, and the nitrogen adsorption-desorption isotherm curves obtained were as follows: Figure 1 The pore size distribution curve is shown in Figure 2 shown.
[0080] Depend on Figure 1 It can be seen that the nitrogen adsorption-desorption isotherms of the porous carbon materials in Examples 1 to 9 are all typical type IV isotherm adsorption curves; in the area of relatively low relative pressure (<0.1), the adsorption amounts of the porous carbon materials in Examples 1 to 9 increase sharply, indicating that there are a large number of microporous structures inside the porous carbon materials in Examples 1 to 9, and when the relative pressure is between 0.4 and 1.0, an H4 type hysteresis loop appears on the curve, indicating that there are crack pores (mesopores) inside the porous carbon material.
[0081] Depend on Figure 2 It can be seen that the pores of the porous carbon materials in Examples 1 to 9 are mainly micropores and small mesopores with a pore size less than 10 nm, and a small amount of large mesopores and macropores are distributed between pore sizes of 10 nm to 50 nm and 50 nm to 70 nm, respectively.
[0082] 2) Cyclic voltammetry test: The electrodes in Examples 1 to 9 were subjected to cyclic voltammetry tests using an electrochemical workstation model CHI660e, with a scanning potential range of -1.0 V to 0 V and a scanning speed of 10 mV / s. The obtained cyclic voltammetry curves are shown in FIG. Figures 3 to 5 shown.
[0083] Depend on Figure 3 It can be seen that the electrodes in Examples 1 to 3 all exhibit typical double-layer capacitance behavior; the electrode in Example 3 has the largest closed area of the CV curve and the best electrochemical activity.
[0084] Depend on Figure 4 It can be seen that the electrodes in Examples 4 to 6 all exhibit typical double-layer capacitance behavior; the electrode in Example 4 has the largest closed area of the CV curve and the best electrochemical activity.
[0085] Depend on Figure 5 It can be seen that the electrodes in Examples 7 to 9 all exhibit typical double-layer capacitance behavior; the electrode in Example 8 has the largest closed area of the CV curve and the best electrochemical activity.
[0086] 3) Constant current charge and discharge test: The electrodes in Examples 1 to 9 were subjected to constant current charge and discharge tests using an electrochemical workstation model CHI660e. The charge and discharge potential range was -1.0 V to 0 V, and the current density was 1 A / g. The constant current charge and discharge curves obtained were as follows: Figures 6 to 8 shown.
[0087] Depend on Figure 6 It can be seen that the constant current charge and discharge curves of the electrodes in Examples 1 to 3 are basically linearly symmetrical isosceles triangles, indicating that their charge and discharge reversibility is good; the electrode in Example 3 has the longest charge and discharge time and the highest specific capacity, reaching 211.6F / g.
[0088] Depend on Figure 7 It can be seen that the constant current charge and discharge curves of the electrodes in Examples 4 to 6 are basically linearly symmetrical isosceles triangles, indicating that their charge and discharge reversibility is good; the electrode in Example 5 has the longest charge and discharge time and the highest specific capacity, reaching 220.1F / g.
[0089] Depend on Figure 8 It can be seen that the constant current charge and discharge curves of the electrodes in Examples 7 to 9 are basically linearly symmetrical isosceles triangles, indicating that their charge and discharge reversibility is good; the electrode in Example 8 has the longest charge and discharge time and the highest specific capacity, reaching 190.9F / g.
[0090] 4) Electrochemical impedance test: Electrochemical impedance test was performed on the electrodes in Examples 1 to 9 using an electrochemical workstation model CHI660e. The frequency range of the AC potential wave was 0.1 Hz to 100,000 Hz. The obtained electrochemical impedance spectrum curve is shown in FIG. Figures 9-11 shown.
[0091] Depend on Fig. 9It can be seen that the intersection points of the electrochemical impedance curves of the electrodes in Examples 1 to 3 are close to the Z′ axis, so their inherent ohmic resistances are relatively close. The high-frequency ring diameter of the electrode in Example 2 is the smallest and the interface impedance is the smallest, followed by the electrode in Example 3. In the low-frequency region, the straight line of the electrode in Example 3 is closer to vertical, indicating that the electrode in Example 3 has a more ideal capacitive diffusion behavior when the inherent ohmic resistance and interface impedance are close.
[0092] Depend on Fig.10 It can be seen that the intersection points of the electrochemical impedance curves of the electrodes in Examples 4 to 6 are close to the Z′ axis, so their inherent ohmic resistances are relatively close. The high-frequency ring diameter of the electrode in Example 6 is the smallest and the interface impedance is the smallest, followed by the electrode in Example 4. In the low-frequency region, the straight line of the electrode in Example 6 is closer to vertical, indicating that the electrode in Example 6 has a more ideal capacitive diffusion behavior when the inherent ohmic resistance and interface impedance are close.
[0093] Depend on Fig.11 It can be seen that the intersection points of the electrochemical impedance curves of the electrodes in Examples 7 to 9 are close to the Z′ axis, so their inherent ohmic resistances are relatively close. The high-frequency ring diameter of the electrode in Example 9 is the smallest and the interface impedance is the smallest, followed by the electrode in Example 7. In the low-frequency region, the straight line of the electrode in Example 7 is closer to vertical, indicating that the electrode in Example 7 has a more ideal capacitive diffusion behavior when the inherent ohmic resistance and interface impedance are close.
[0094] The yields of the porous carbon materials in Examples 1 to 9 and Comparative Examples 1 to 2 and the performance summary data of the electrodes in Examples 1 to 9 are shown in the following table:
[0095] Table 1 Summary of porous carbon material yield and electrode performance
[0096]
[0097]
[0098] Note:
[0099] The calculation formula for the yield of porous carbon material is as follows: yield of porous carbon material (%) = m2 / m1×100%, m1 is the weight of indigo, and m2 is the weight of porous carbon material.
[0100] From Table 1, we can see that:
[0101] a) The present invention uses indigo as a precursor and ferric chloride as an activator to prepare a porous carbon material, and the yield of the porous carbon material can reach more than 80%, while the yield of the porous carbon material is lower than 45% when a common molten salt (sodium carbonate or potassium carbonate) is used as an activator to prepare a porous carbon material;
[0102] b) The mass ratio of indigo and ferric chloride and the pyrolysis temperature will directly affect the yield and electrochemical performance of porous carbon materials;
[0103] c) At the same mass ratio of indigo and ferric chloride, the higher the pyrolysis temperature, the lower the yield of porous carbon material;
[0104] d) At the same pyrolysis temperature, the yield of porous carbon material is highest when the mass ratio of indigo to ferric chloride is 1:3.
[0105] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a porous carbon material, characterized in that: The following steps are involved: The indigo and ferric chloride are mixed and pyrolyzed in a protective atmosphere to obtain a porous carbon material.
2. The method for preparing a porous carbon material according to claim 1, characterized in that: The mass ratio of indigo to ferric chloride is 1:0.1-10.
3. The method for preparing a porous carbon material according to claim 1 or 2, characterized in that: The protective atmosphere is a nitrogen atmosphere or an argon atmosphere.
4. The method for preparing a porous carbon material according to claim 1 or 2, characterized in that: The pyrolysis is carried out at a temperature of 300° C. to 1500° C., and the pyrolysis time is 0.5 h to 5 h.
5. The method for preparing a porous carbon material according to claim 1 or 2, characterized in that: The product obtained by the pyrolysis is further acid-washed, water-washed and dried.
6. The method for preparing a porous carbon material according to claim 5, characterized in that: The acid solution used in the pickling is one of hydrochloric acid, sulfuric acid and nitric acid.
7. The method for preparing a porous carbon material according to claim 5, characterized in that: The concentration of the acid solution used in the pickling is 0.1 mol / L to 3.0 mol / L.
8. An electrode, characterized in that: The porous carbon material comprises a porous carbon material prepared by the method according to any one of claims 1 to 7.
9. A supercapacitor, characterized in that: Comprising the electrode according to claim 8.
10. A lithium ion battery, characterized in that: Comprising the electrode according to claim 8.
Citation Information
Patent Citations
Nitrogen and sulfur co-doped carbon@FeS nanotube as well as preparation method and application thereof
CN112408496A
Porous carbon material as well as preparation method and application thereof
CN118183733A
Cited By
Stainless steel carbon deposition electrode and preparation method and application thereof
CN120987458A
Preparation method of iron-nitrogen co-doped porous carbon material
CN121651359A